FAKTOR-FAKTOR YANG MEMENGARUHI KETEPATANWAKTU PENYAMPAIAN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH (SKPD) KE PEJABAT PENGELOLA KEUANGAN DAERAH (PPKD) KABUPATEN POLEWALI MANDAR - Jaya, Andi Ilham; Ruliaty, Ruliaty (COMPETITIVENESS, 2019)
AbstractThis study aims to analyze and know 1) human resource education factors affect the timeliness of financial statements delivery, 2) training factors affect the timeliness of financial statements delivery, 3) information technology utilization factors affect the timeliness of financial statements delivery, and 4) regulatory understanding factors affect the timeliness of the delivery of SKPD financial statements to PPKD Polewali Mandar Regency. The data used in this study were primary data obtained from questionnaires. The population of 47 SKPD, and based on purposive sampling with sample criteria taken in this study are employees who carry out financial management including the Head of Office / Agency / Office ranging from the Office of Financial Administration (PPK), Technical Implementation Officer of Activities (PPTK), Treasurer of Expenditure and Assistant Treasurer. The data obtained is processed using multiple linear regression analysis. The results of this study show that: 1) Education has a significant effect on the timeliness of the delivery of financial statements. 2) Training has no significant effect on the timeliness of financial statements. 3) The utilization of information technology has no significant effect on the timeliness of the delivery of financial statements and 4) Understanding of regulations has no significant effect on the timeliness of the submission of financial statements from SKPD to PPKD Polewali Mandar Regency. Keywords: Timeliness, Financial Statements, and Financial Management